Análise do transporte gratuito de estudantes das universidades públicas: estudo de caso UFERSA Campus Pau dos Ferros-RN - Rodrigues, Francisco Raí Alves (Universidade Federal Rural do Semi-Árido, 2018)
With the expansion and diffusion of university education throughout Brazil, several university campuses were established in inner cities, classified as medium or small. These cities, on the other hand, do not have a good infrastructure, capable of supporting a new flow generated by these educational establishments, triggering several other deficiencies, such as the lack of student housing, supermarkets, restaurants and even a local public transport system. Thus, the study has as a research line a study of collective transportation for the exclusive use of students of the Federal University of the Semi-Arid-UFERSA, Pau dos Ferros-RN campus. The research was carried out by reviewing the specific literature and quantitative and qualitative research developed in the field to examine and provide a better understanding of the problem of this work, given the situations and experiences of UFERSA students interviewed regarding the conditions of free collective transportation offered by the institution. The surveys indicated the degree of student satisfaction regarding the routes served by transportation, schedules and drivers' performance. However, they indicated the need for solutions in terms of overcrowding, mainly in the schedules with the highest number of classes offered.
Keywords: Transporte público; Planejamento; Transporte escolar; ENGENHARIAS::ENGENHARIA CIVIL